Mycotoxins in grain and grain products in South Africa and proposals for their regulation - Viljoen, Jan Hendrik (University of Pretoria, 2013)
The purpose of the study was to: ° Report on the occurrence of mycotoxins in grain and grain products in South Africa; ° Compare with other countries; ° Weigh the evidence regarding effects on health of test animals, and human and animal consumers; ° Determine the need for statutory measures to regulate mycotoxins in food; and ° Propose practical measures for controlling mycotoxins in grain and grain products in South Afica. Good mycotoxin data for maize were obtained from the author's surveys. Data on other local grains is lacking. In domestic maize, fumonisins and deoxynivalenol occur regularly, at levels as low or lower than in Argentina and the USA. Other mycotoxins occur rarely, or at very low levels. Deoxynivalenol is likely to occur regularly in domestic wheat. Aflatoxins were virtually absent in domestic maize, but often occur at concerning levels in imported Argentinean and USA maize. The literature show that aflatoxins are acutely and chronically toxic to humans and animals and most countries maintain regulatory Maximum Tolerable Levels (MTLs) for aflatoxins in grain and grain products. Several countries also maintain regulatory MTLs for deoxynivalenol, based on lesser scientific evidence. The mycotoxin that occurs most frequently in South African maize, is the fumonisin B group of analogues, with fumonisin B1 the most abundant. Fumonisins are produced by Fusarium verticillioides (previously known as Fusarium moniliforme) and occur in maize worldwide. Fumonisins cause leukoencephalomalacia in horses, pulmonary oedema in pigs, liver cancer in rats and liver and kidney damage in other animals. A statistical relationship between the occurrence of F. verticillioides and fumonisins in maize and oesophageal cancer in humans has been demonstrated in Transkei and in China. The 'toxins derived from F. moniliforme' and fumonisin B1 have been evaluated as Group 2B carcinogens i.e. possibly carcinogenic to humans, by the International Agency for Research on Cancer of the World Health Organisation. Based on a review of epidemiological and toxicological evidence of the effects of fumonisins on humans and animals, their occurrence in maize and maize products, previously proposed MTLs, and the practical implications of MTLs set for maize and maize products, we propose the following MTLs for total fumonisins in maize and maize products for human consumption: ° 4 µg/g in whole, uncleaned maize; ° 2 µg/g in dry-milled maize products with fat content of >3.0 %, dry weight basis (e.g., sifted and unsifted maize meal); and ° 1 µg/g in dry-milled maize products with fat content of <3.0 %, dry weight basis (e.g., flaking grits, brewers grits, samp, maize rice, super and special maize meal) These MTLs are too high to address a possible link of fumonisins with neural tube defects in neonates. This potential problem remains to be addressed, possibly by fortification of maize products with folic acid. We propose MTLs for deoxynivalenol of 2 µg/g in cereal grains for food use, and 1 µg/g in cereal grain food products. Finally, we propose that the current regulatory MTLs for aflatoxins be raised from 10 ng/g (total aflatoxins in unprocessed maize) to 20 ng/g. === Dissertation (PhD)--University of Pretoria, 2003. === Microbiology and Plant Pathology === Unrestricted